Single-Port Transaxillary Robotic Bilateral Total Thyroidectomy (START) for Graves’ Disease: First Initial 10 Cases Using da Vinci SP Robotic System - Lee, In A; Kim, Jin Kyong; Lee, Cho Rok; Kang, Sang-Wook; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn (Journal of endocrine surgery, 2022)
Purpose: Graves’ disease (GD) is an autoimmune disorder and the most common cause of persistent hyperthyroidism. Recently, robotic transaxillary thyroidectomy has served as a minimally invasive surgical alternative to conventional open thyroidectomy, even for patients with GD. In 2019, we first performed single-port transaxillary bilateral total thyroidectomy using the da Vinci SP robotic system (START). This study aimed to evaluate the technical feasibility of START for GD. Methods: This retrospective review included 10 patients with GD who underwent START at our institution between September 2020 and January 2022 by a single surgeon. Results: All 10 patients were female, and the body-mass index was 22.3±3.6 kg/m2 (range, 18.6–28.9). Seven patients (70%) had thyroid carcinoma, two (20%) had persistent hyperthyroidism despite medical control, and one patient (10%) had Graves’ ophthalmopathy. The mean operation time was 173.4±26.8 min (range, 128–226), and the mean estimated blood loss was 102.0±185.1 mL (range, 10–600). There were no cases of conversion to open surgery. There were no intraoperative complications and six cases of postoperative complications, including transient hypocalcemia in three cases, bleeding with reoperation in two cases, and transient hoarseness in one case. Conclusions: Patients with GD with large goiter and hypervascularity require delicate ligation, even of minor vessels, in a narrow space. START is feasible and safe for GD performed by high-volume expert surgeons. KCI Citation Count: 1